THE INFLUENCE OF SOCIAL MEDIA ON INVESTMENT INTEREST IN CRYPTO CURRENCY - Abbas, Abbas; Dewi, Andi Ratna Sari; Latiep, Ifah Finatry; Rachman, Abdul Nasir; Armilsar, Tri Ayu Lestari Putri; Hardiyono, Hardiyono (Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study aims to analyze the influence of social media on investment interest in cryptocurrencies, focusing on the role of influencers, psychological factors, and demographic characteristics. Using a quantitative approach through an online survey of younger respondents, the results show that social media has a significant effect on crypto investment interest. Exposure to influencer content has been shown to drive investment decisions, even when financial literacy and investment experience are not the dominant factors. In addition, risk aversion has a negative influence on investment interest, while skepticism is insignificant. Generation Z and millennials are recorded as the most active group in crypto investments, with social media as the main source of information. These findings imply the need for a new approach in financial education that focuses not only on basic literacy, but also on the critical ability to assess digital content and identify potential manipulation